Employer branding practices amongst the most attractive employers of the IT and engineering sector in Portugal - Gregorka, Lea (2017)
Employer branding is a marketing strategy that helps employers to keep competitive in their markets. Although it is a concept used for over 30 years, its process and consequences have not yet been fully scrutinized. This study characterizes the employer branding implementation process and the employers’ perspective on it. We detailed not only how employer branding practices are applied, but also the role of Human Resources Management in the process and the used practices for employee attraction and retention. We conducted ten semi-structured, in-depth interviews amongst the Human Resources departments of the most attractive employers in the IT and Engineering sector in Portugal to gather insights about their current employer branding processes. The collected data was analyzed with the the qualitative method of thematic analysis. The research indicates that although the employer branding process is not a clearly structured process, some stages can be identified as common. For that reason, we propose a stage divided framework for the employer branding process and we also highlight each one of the identified stages. However, we concluded that there is no universal employer branding formula since different practices of employer branding are used according to several employer branding’s objectives and desired perception by the market. The results suggest that in order to achieve these outcomes employers adapt their employee value proposition. These offers have a common base, but unique additional factors, which confirm the employer’s differentiation and, as the previous literature had concluded, a stronger employer brand. On the other hand, Human Resources departments have a leading role in employer branding, however a collaboration between all the departments involved is crucial. Finally, future investigation for particular stages of the employer branding process were suggested, as well as doing separate studies for the IT and the engineering areas.